Analisis Gharar Dalam Obyek Jual Beli Online - Zamah syari, Mohamad Ainun Najib; Muhammad Abduh (STAI Al-Mas'udiyah, 2023)
Ease of doing business online, bringing up creative business ideas in marketing business products, or selling various business products, including the practice of dropshipping and mystery boxes. This research will discuss the practice of gharar in online buying and selling in the form of dropship and mystery boxes. This research is a type of descriptive qualitative research. which aims to understand the phenomenon or occurrence of buying and selling online in the form of dropship and mystery box in depth and descriptive. The results of this study are that the continuity of the handover of dropship products to buyers still depends on ownership or full authority over the goods being traded. Dropshipp does not interpret aspects of legal ownership of goods. This can cause uncertainty (gharar) in the handover of goods to buyers, the availability of goods and time. Uncertainty in mystery box products can also contribute to greater risk. The equilibrium point in a mystery box product is not the result of the intersection of supply and demand with the same quality. This means that the level of balance that is created is an apparent balance because it brings together demand and supply that differ in quality.